The gravity of high-skilled migration policies - Czaika, M; Parsons, C (International Migration Institute, 2015)
Despite the almost ubiquitously held belief among policy makers that immigration policies aimed at attracting high-skilled workers meet their desired aims, academics continue to debate their efficacy. This paper presents the first judicious assessment on the effectiveness of such policies. We combine a unique new data set of annual bilateral high-skilled immigration labour flows for 10 OECD destinations between 2000 and 2012, with new databases comprising both unilateral and bilateral policy instruments, to examine which types, and combinations, of policies are most effective in attracting and selecting high skilled workers using a micro-founded gravity framework. Points-based systems are much more effective in attracting and selecting high-skilled migrants in comparison with requiring a job offer, labour market tests or working in shortage-listed occupations. Financial incentives yield better outcomes in 'demand-driven’ systems than when combined with points-based systems however. Offers of permanent residency, while attracting the highly skilled, overall reduce the human capital content of labour flows since they prove more attractive to non-high skilled workers. Bilateral recognition of diploma and social security agreements, foster greater flows of high skilled workers and improve the skill selectivity of immigrant flows. Conversely, double taxation agreements deter high-skilled migrants, although they do not alter the overall skill selectivity. Higher skilled wages increase the number and skill selectivity of labour flows, whereas higher levels of unemployment exert the opposite effects. Migrant networks, contiguous borders, common language and freedom of movement, while encouraging greater numbers of high skilled workers, exert greater effects on non-high skilled workers, thereby reducing the skill content of labour flows. Greater geographic distances however, while deterring both types of workers, affect the high skilled less, thereby improving the selection on skills. Our results are robust to a variety of empirical specifications, accounting for destination-specific amenities, multilateral resistance to migration and the endogeneity of immigration policies.